2009
DOI: 10.1177/0734242x07081483
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of collagen and gelatine from meat industry by-products for food and non food uses

Abstract: Short tendons of slaughtered cattle, which consist of relatively pure collagen, were cleaned of lipoid substances and non-collagen proteins using a commercial enzymatic preparation. Diluted acetic acid was used to separate the acid-soluble collagen (M(N) approximately 300 kDa) for a yield of around 5%. The residue was extracted with water and the extraction conditions were derived to produce gelatine with a gel rigidity of 350-410 degrees Bloom and a yield of 55-60%. Prolonged extraction time, as well as incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Research has also demonstrated a beneficial effect of synthetic peptides and total protein extracts on wound healing (Bentley et al, 1990) and on the production of new collagen fibers (Katayama et al, 1993). However, most of these peptide and aminoacid mixtures used as ingredients in cosmetics contain either chemically synthesized peptides, or peptides obtained by the partial digestion of animal proteins, like collagen and elastin (Mokrejs et al, 2009;Langmaier et al, 2002). The use of peptides produced by hydrolysis of animal proteins always involves certain risks associated with the use of any product derived from animals.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also demonstrated a beneficial effect of synthetic peptides and total protein extracts on wound healing (Bentley et al, 1990) and on the production of new collagen fibers (Katayama et al, 1993). However, most of these peptide and aminoacid mixtures used as ingredients in cosmetics contain either chemically synthesized peptides, or peptides obtained by the partial digestion of animal proteins, like collagen and elastin (Mokrejs et al, 2009;Langmaier et al, 2002). The use of peptides produced by hydrolysis of animal proteins always involves certain risks associated with the use of any product derived from animals.…”
Section: Introductionmentioning
confidence: 99%
“…The meat processing industry produces considerable quantities of slaughter by-products every year. They are highly underutilised and regarded as huge wastes and potential pollution to the environment (Mokrejs et al, 2009). Connective tissue, accounting for 9-12% of meat by weight, is a major constituent of meat slaughter and processing by-products (Jayathilakan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Collagen does not express antigenicity in physiological conditions, it is completely resorbable in vivo and its physicochemical properties can be suitably controlled. Because of its unique biological and functional properties, collagen has been widely applied in food, cosmetic, base for smart hydrogels and medicine [8][9][10][11][12][13] . At the present there is wide interest in collagen as biomaterials.…”
Section: Introductionmentioning
confidence: 99%